How to achieve subjective well-being through medical tourism: the engagement process through credibility, desire and experience - Loureiro, S. M. C.; Panchapakesan, P. (Advances in Psychology Research, 2016)
Medical tourism or health treatment made outside the native country for maintaining, restoring or enhancing the body or the mind, has become an economic activity of growing interest in Europe and Asia. This treatment may span the full range of medical services, but most commonly includes dental care, cosmetic surgery, elective surgery, and fertility treatment, which are either time-consuming or illegal in certain developed countries. Yet, how consumers’ desires for this medical treatment abroad lead to the engagement process has not been studied and analyzed. The current chapter intends to propose a conceptual theoretical framework that presents antecedents (i.e., ideal, social and actual image, past experience, credibility and involvement) of consumers’ desire and engagement (i.e., involvement, experience, relationship quality) in medical tourism practices, as well as outcomes (i.e., brand behavior and subjective well-being). The framework also suggests several moderators such as gender, age, self-esteem, national culture, and job engagement that can either strengthen or weaken the established relationships. Finally, the chapter points out potential managerial implications and avenues for further research.